Perbandingan Efisiensi Energi dan Kualitas Produk pada Teknologi Termal Pirolisis dan Gasifikasi Sampah Plastik: Studi Literatur - Noverly Arisani, Shelly; Mila Dirgawati; Novi Fitria (Jurnal Serambi Engineering, 2025)
The problem of plastic waste generation is increasingly pressing in Indonesia. Thermal technology offers an alternative solution that is more environmentally friendly in managing plastic waste. This literature study aims to compare pyrolysis and gasification technologies in converting plastic waste into energy. The analysis was carried out by reviewing various relevant studies. The results of the study indicate that both technologies have the potential to reduce plastic waste generation and produce value-added products. Pyrolysis is a thermal decomposition process without oxygen that produces oil, gas, and charcoal. Gasification produces syngas that can be used as fuel. This process requires limited oxygen and produces more diverse emissions. The comparison between pyrolysis and gasification shows that the selection of the right technology depends on several factors, such as the type of plastic, the desired product quality, and environmental considerations. Pyrolysis is more suitable for oil production, while gasification is more flexible in producing various types of gas products. Overall, both pyrolysis and gasification have great potential in managing plastic waste. However, further research is needed to optimize the process and reduce environmental impacts. Thus, thermal technology can be a sustainable solution in overcoming the problem of plastic waste in Indonesia.